COMPONENTS FROM VARIOUS BIOLOGICAL SOURCES REDUCES THE TOXIC EFFECTS OF COPPER SULPHATE IN OLD ANIMALS - Ivanov , Evgeny; Akzhyhitov , Rustam; Bozhkov , Anatoly (Collection of scientific papers «ΛΌГOΣ», 2024)
We investigated the possibility of eliminating the toxic effect of copper sulfate on the body of young (3 m.) and very old (30 m.) Wistar rats through preliminary repeated (over 7 days) administrations of multicomponent BAS (cow colostrum or components of the fungi Pleurotus ostreatus and Sacharomyces cerevisue). The time of death of the animals, the presence of chronic pathologies, as well as a complete blood count were determined. It was shown that preliminary repeated administration of biologically active substances to animals contributed to an increase in the survival rate of old animals.